Translatology: Interrogative Musings on the Grid - Giridhar, P. (Meta, 2005)
AbstractThis essay attempts some regurgitation of what has been happening in TS these days. It argues that Translatology has culpably failed to address issues and has instead moved around without quite getting things into a rational perspective. It argues that the putative opposition of the ‘linguistic turn’ and the ‘cultural turn’ in TS is misplaced, by spotlighting the language-nonlanguage dialectic. (Rajendra Singh (2005) argues for a ‘re-turn’). Translatology has culpably failed to work toward the rigour that characterizes, or should characterize, all academic disciplines. This piece is a plea for more rigour and less hyperactivity in TS. That there is as yet no theory of translation is unarguable. None is there to be sighted on the horizon. I don’t agree with Peter Newmark on the other hand that there can be no laws or theory of translation. That is too strong a position to take it seems to me. (Equally obvious is the averral that there is no theory of literature. ‘Theory’ is too strong a word to use for whatever exists as a set of organizing or underpinning principles that govern the phenomenon of literature.) Whatever TS theory may be said to exist lacks muscle tone in a way in which Nuclear Physics, for example, does not. That Nuclear Physics is a physical or natural science and TS is Humanities is no argument. The point is that anything that is unconstrained in an absolute sense, in a transcendent sense cannot be piquant in any meaningful sense. Unbridled or barely bridled creativity cannot be meaning-making. Absolutely untrammeled centrifugality where everything and anything ‘goes’ is in point of fact an intellectually vacuous exercise. The ‘cultural turn’ in its strong version effects a radical change in the ‘enabling function’ of translation and converts the ‘traces’ of the translator’s presence into a massively visible one. At the least the ‘cultural turn’ is misstated and, in a sense, which I hope to make clear, overstated in the sense of throwing the floodgates open, which isn’t a hallmark of an academic discipline. Attempting an elucidation of why things are the way they are in TS the note concludes that TS must strive toward a crosslinguistically and crossculturally valid discourse about translation, a discourse grounded in, sanctioned by, driven and underpinned by a well-founded, crossculturally valid but subject-to-rational-change grid. This piece is intended therefore as a corrector and some kind of a reiner. As indicated at places what is said about translation applies equally to literature. The piece would have served its purpose if the interrogatives get home. The answers could take a while to come by.